Fetal and Neonatal Outcomes of Antenatally Detected Ductus Arteriosus Aneurysm: A Retrospective Observational Study - Redishetty, Saritha; Mohanty, Shristy; Kolar, Geeta; Vavilala, Suseela (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVE: Ductus arteriosus aneurysm (DAA) is a rare fetal cardiac anomaly characterized by abnormal dilation of the ductus arteriosus. While many cases resolve spontaneously, DAA can be associated with complications such as thromboembolism, rupture, or persistent patent ductus arteriosus (PDA). The increasing use of fetal echocardiography has improved early diagnosis, but the clinical significance and outcomes of antenatally diagnosed DAA remain incompletely understood. This study aims to analyze the prevalence, echocardiographic characteristics, and postnatal outcomes of antenatally diagnosed DAA, as well as evaluate the association between DAA size, maternal and neonatal factors, and postnatal PDA persistence. STUDY DESIGN: This retrospective observational study was conducted at a tertiary care perinatal center in South India from 2011 to the present. All third-trimester fetuses diagnosed with DAA via ultrasound were included. Data on maternal and neonatal characteristics, postnatal echocardiographic findings, and perinatal outcomes were collected and analyzed. Statistical analysis was performed using SPSS version 26, with significance set at p<0.05. RESULTS: A total of 35 foetuses were diagnosed with DAA. The mean maternal age was 26.32 ± 9.33 years, and the mean gestational age at delivery was 34.34 ± 3.58 weeks. Spontaneous resolution of DAA occurred in 62.85% of cases, while 17.14% had juxta-ductal coarctation with moderate PDA, 11.42% had DAA with an organized thrombus, and 8.57% had a large ductal aneurysm with a small PDA. Larger DAA size was significantly associated with persistent PDA (p=0.009). Lower gestational age was also a significant predictor of PDA persistence (p=0.03), whereas birth weight and maternal age showed no significant associations. CONCLUSION: The majority of antenatally diagnosed DAA cases resolve spontaneously, but larger aneurysms and lower gestational age are associated with persistent PDA. These findings highlight the importance of prenatal and postnatal echocardiographic surveillance for risk stratification and management. A conservative yet vigilant approach is recommended to optimize neonatal outcomes.